2008
DOI: 10.1002/hep.22316
|View full text |Cite
|
Sign up to set email alerts
|

Retinol‐binding protein 4: A new marker of virus‐induced steatosis in patients infected with hepatitis c virus genotype 1

Abstract: Retinol-binding protein 4 (RBP4) is an adipocytokine associated with insulin resistance (IR).We tested serum levels of RBP4 to assess its link with steatosis in patients with genotype 1 chronic hepatitis C (CHC) or nonalcoholic fatty liver disease (NAFLD). Nondiabetic patients with CHC (n ‫؍‬ 143) or NAFLD (n ‫؍‬ 37) were evaluated by liver biopsy and anthropometric and metabolic measurements, including IR by the homeostasis model assessment. Biopsies were scored by Scheuer classification for CHC, and Kleiner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 46 publications
5
53
2
Order By: Relevance
“…Our population had a low prevalence of obesity (15%), but nonetheless 26% of patients had diabetes, and the mean HOMA-IR score was approximately 4, higher than observed in our previous studies of subjects with chronic hepatitis C. 32,36 The high prevalence of diabetes and the high HOMA-IR values were not likely attributable to a "hepatogenous diabetes," 43 considering that they were found in a cohort of Child A patients. We identified an HOMA-IR score of greater than 3.5 as the cutoff value with the best sensitivity and specificity for predicting EV presence.…”
Section: Discussionmentioning
confidence: 75%
“…Our population had a low prevalence of obesity (15%), but nonetheless 26% of patients had diabetes, and the mean HOMA-IR score was approximately 4, higher than observed in our previous studies of subjects with chronic hepatitis C. 32,36 The high prevalence of diabetes and the high HOMA-IR values were not likely attributable to a "hepatogenous diabetes," 43 considering that they were found in a cohort of Child A patients. We identified an HOMA-IR score of greater than 3.5 as the cutoff value with the best sensitivity and specificity for predicting EV presence.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, both animal and human studies have shown that RBP4 might be involved in the development of insulin resis- tance and diabetes 24,25) . Furthermore, serum RBP4 levels have been shown to be associated with the degree of steatosis and fibrosis in liver diseases and chronic hepatitis C 26,27) . Considering the association between depressed serum RBP4 and hepatic damage, and the liver pathology of perivascular infiltrates and fibrosis in TCE-induced autoimmune hepatitis in MRL+/+ mice 28) , further studies are needed to investigate the precise role of RBP4 in the hepatotoxicity in THD.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, the literature has suggested linkages between serum RBP4 concentrations, obesity, impaired insulin responsiveness (103)(104)(105)(106)(107)132 ), fatty liver development (134)(135)(136)(137)(138)(139)(140), vessel wall disease ( 141,142 ), and heart disease ( 143 ). At the molecular level, the best studied of these effects is the action of excessive RBP4 acting as a cytokine activating a signaling cascade within cells, which can eventually lead to both direct and indirect alterations in insulin signaling.…”
Section: Retinoids In Adipose Tissuementioning
confidence: 99%